2021
DOI: 10.3390/polym13010157
|View full text |Cite
|
Sign up to set email alerts
|

Dental 3D-Printing: Transferring Art from the Laboratories to the Clinics

Abstract: The rise of three-dimensional (3D) printing technology has changed the face of dentistry over the past decade. 3D printing is a versatile technique that allows the fabrication of fully automated, tailor-made treatment plans, thereby delivering personalized dental devices and aids to the patients. It is highly efficient, reproducible, and provides fast and accurate results in an affordable manner. With persistent efforts among dentists for refining their practice, dental clinics are now acclimatizing from conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(126 citation statements)
references
References 165 publications
0
90
0
7
Order By: Relevance
“…Manufacturing dental prostheses using additive 3D printing technology reduces material waste and allows the processing of multiple prostheses simultaneously [5,14]. Prostheses fabricated using 3D printing were found in a recent study to have similar precision to those fabricated using milling or conventional techniques [15][16][17][18][19]. Due to the aforementioned advantages, 3D printed resin materials can be an alternative to CAD/CAM milling materials for dental applications.…”
Section: Introductionmentioning
confidence: 99%
“…Manufacturing dental prostheses using additive 3D printing technology reduces material waste and allows the processing of multiple prostheses simultaneously [5,14]. Prostheses fabricated using 3D printing were found in a recent study to have similar precision to those fabricated using milling or conventional techniques [15][16][17][18][19]. Due to the aforementioned advantages, 3D printed resin materials can be an alternative to CAD/CAM milling materials for dental applications.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that with proper analysis, the current designs can be improved towards the higher resiliency of biomedical devices applied intraorally. Three-dimensional biocompatible printing can achieve outputs which are not only biomechanically fully functional but are also more effective than handmade devices [25][26][27][28][29][30]. Results of this study revealed that redesigning the shapes in concordance with biocompatible material properties can provide a more resilient device.…”
Section: Discussionmentioning
confidence: 99%
“…According to a 2019 review, nearly 1322 articles are published based on 3D-printed dental implants, pointing towards the scope of AM in dentistry. Most commonly used are titanium/alloys, nickel alloys, and cobalt-chromium; however, nickel alloys are sidelined in current clinical practice due to allergic reactions it triggers [ 207 ]. Milling was one of the conventional techniques used in CoCr dental prosthesis manufacturing; however, metal shrinking is a common shortcoming with this technique, which can be eliminated in 3D printing [ 208 , 209 ].…”
Section: Metal-based Am With Added Functionalities and Applicationmentioning
confidence: 99%